THEORETICAL AND LEGAL INNOVATIONS OF TEACHING INFORMATION LAW IN HIGHER EDUCATIONAL ESTABLISHMENTS OF UKRAINE (Bulletin of Kharkiv National University of Internal Affairs, 2018)
The issue of the formation of advanced theoretical legal doctrines within information law has been studied, where the author has distinguished the following: the branch doctrine of information law in the system of national law and legislation; doctrine of broad interpretation of the right to information; extraordinary concept of the object of information and legal relations; doctrine about specific subjects of information and legal relations; the concept of legal principles of information community; theory of informational sovereignty of the state; doctrine about information and legal liability. It has been stated that these concepts provide new understanding of the subjective and object composition of information, legal relations, develop legal theory about information community. Interrelation of these concepts with information relations promotes the formation of scientific school of the theory of information law.The author has grounded the opinion on the need to implement into educational process of covered in this article achievements of such scholars as A. A. Pesmenytskyi, V. S. Tsymbaliuk, O. S. Denisova, O. S. Rozhdestvenska, V. D. Suprun, S. V. Stasiuk, V. D. Hapotii, who examined various problems of information and legal relations.The author has emphasized that Ukraine urgently needs the experts in legal, journalistic direction, specialists in public relations, teachers in fundamentals of law and others with informational and media specializations that should facilitate the formation of information community in Ukraine and increase the rating of the country in the international information space
Keywords: information law; innovations within information law; subjects of information legal relations; information community; information and legal liability